L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Number: 25
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Queer studies: A lesbian, gay, bisexual & transgender anthology - Beemyn, Genny; Eliason, Michele J. (New York University Press, 1996)
This book is a wide-ranging anthology which discusses the nature and diversity of queer studies, its foundations, and some of the most pressing issues in the field.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identité sexuelle; identités; identités LGBTQIA2+; philosophie politique; postmodernisme; premier cycle; queer; sciences humaines; sex3383; sexualité; sociologie; thématiques

Love and Intimacy: The Gender Division of Emotion and 'Emotion Work': A Neglected Aspect of Sociological Discussion of Heterosexual Relationships - Duncombe, Jean; Marsden, Dennis (Sociology, 1993)
This paper discusses the role of ideologies of love and intimacy in heterosexual coupledom, and examines the applicability of theories of the gender division of 'emotion work' to the field of intimate personal relationships. Research on the private sphere of the family has recently focused on quantifying instrumental aspects of relationships, such as financial management, the domestic division of labour and informal care. However, although fruitful, such approaches neglect the expressive or emotional; particularly the experiences of love and intimacy, which many people say they regard as a key element in their personal relationships. We suggest reasons for British sociology's neglect of what is almost a cliche in everyday discourse. And we present evidence (including preliminary findings from our own research on heterosexual couples) that - despite dissatisfaction with gender inequalities in domestic tasks and finance - many women express unhappiness primarily with what they perceive as men's unwillingness or incapacity to `do' the emotional intimacy which appears to them necessary to sustain close heterosexual couple relationships. We illustrate how similar discussions of gender differences in emotional behaviour have emerged elsewhere (including in the new masculinity literature), raising questions about how far men's and women's emotional behaviour can and should change.; The exploration of socially-regulated or `managed' gender divisions in intimate emotional behaviour entails two related but distinct questions: are men and women equally `susceptible' to the emotions or discourses of love and intimacy; and, do they handle such emotions in similar ways in the context of close personal relationships. We suggest how research findings on heterosexual couple relationships can be linked to work on the social regulation of emotion, which argues that there is a `gender division of emotion work' where it is assumed that women will take responsibility for the management of emotion in the private sphere.
Keywords: 1900-1999; 1980-1989; angleterre; approches et analyses; care; cours; discipline; emotional labor; europe; hétérosexualité; postmodernisme; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; thématiques; travail

Sexual practice/textual theory: Lesbian cultural criticism - Wolfe, Susan J.; Penelope, Julia (B. Blackwell, 1993)
Nous vivons à l'ère postmoderniste, poststructuraliste (et, diraient certain.e.s, postféministe), à ​​une époque où le terme lesbienne pose problème, même lorsqu'il est utilisé de manière non péjorative par une lesbienne autoproclamée. Nous ne pouvons plus parler en tant qu'« individus », semble-t-il ; le faire est d’une naïveté et/ou d’une simplicité impardonnable. Nous ne pouvons parler qu'en tant que « sujets » romancés, nos identités individuelles n'existant que comme la création de textes (de quelqu'un) ou comme le résultat d'une signification. En cent ans, les sexologues allemand.e.s ont « apparu » les lesbiennes pour nous pathologiser et les poststructuralistes français.e.s nous ont « fait disparaître » pour déconstruire les catégories de sexe et de genre et « interroger » « le » sujet. Certains universitaires suggèrent que le féminisme et le postmodernisme ont de nombreux points communs. Les théoricien.nes du postmodernisme des deux côtés de l’Atlantique affirment de la même manière que leur mouvement partage un agenda politique avec le féminisme, dans la mesure où déstabiliser les relations narratives entre dominant.e et subordonné.e, contenant et contenu, c’est aussi déstabiliser les relations sociales et culturelles de domination et de confinement en dans lequel le masculin conventionnel subsume et enveloppe le féminin conventionnel. Dans le jargon actuel, le postmodemisme et le féminisme ont « problématisé les relations de genre », remettant en question le « caractère naturel » des relations de genre et considérant la relation entre les sexes comme le résultat de forces sociales, de langage et/ou de pouvoir (Giroux, 28). ). Ni « l'homme » ni la « femme » ne sont un objet ontologiquement stable, une catégorie invariable ; les deux sont construits dans l’histoire (Fuss, 3). Nous ne contesterons pas l’idée que le terme Lesbienne, pendant la brève période où il a été utilisé, a souvent été un terme d’opprobre et non d’approbation – qu’il a été utilisé linguistiquement pour signifier la déviance et même la monstruosité. Nous ne souhaitons pas non plus tomber dans le genre d’essentialisme qui supposerait que toutes les lesbiennes sont « simplement » des lesbiennes. Nous sommes membres de différentes races, classes, groupes ethniques ; collectivement, les lesbiennes souffrent de nombreuses formes d’oppression. En revanche, la philosophie postmoderne, du moins dans les formes qu'elle a prises au sein des instances du pouvoir (pédagogie académique, théorie esthétique et critique) nous semble menacer d'effacer le réel (ou, comme diraient les postmodernistes, « » matériel ») Lesbiennes. Si l’identité est construite par des textes, peut-être n’existe-t-il pas de personne (« objet ») comme lesbienne, aucune caractéristique (non construite) que partagent les lesbiennes. Si les textes et l'identité individuelle peuvent être déconstruits, peut-être que n'importe qui, même non-lesbienne, pourra « lire comme une lesbienne », comme certains l'ont suggéré. Mais s’il n’y a pas d’identité lesbienne en tant que telle, alors l’affirmation selon laquelle on « lit en tant que lesbienne » est un non-sens. Le discours postmoderniste cherche à déplacer les notions humanistes libérales du soi, du « sujet bourgeois » (H. Foster, 77, cité dans Waugh, 8). Mais comme le note Waugh (8-9), le moi unifié postulé par l’humanisme libéral n’était/n’est pas un moi féminin, et encore moins un moi lesbien. La subjectivité, historiquement construite et exprimée à travers l'équation phénoménologique soi/autre, repose nécessairement sur l'« altérité » féminine de l'« individuité » masculine. Le centre subjectif des discours socialement dominants (du « je » philosophique et rationnel de Descartes au phallique/symbolique psychanalytique de Lacan) en termes de pouvoir, d'action et d'autonomie a été un sujet « universel » qui a établi son identité à travers la marginalisation ou l'exclusion invisible de ce qu'elle a également défini comme la « féminité » (qu'il s'agisse du non-rationnel, du corps, des émotions ou du pré-symbolique). Le « féminin » devient ainsi ce qui ne peut s'exprimer parce qu'il existe en dehors du domaine de la signification symbolique. Constitué à travers un regard masculin et donc doté du mystère de celui dont le statut objectif est perçu comme absolu et définitif. Un . . . devient une femme... Dans la relation dialectique entre l'humanisme traditionnel et l'antihumanisme postmoderne apparu dans les années 1960, les femmes continuent d'être déplacées. Comment peuvent-ils aspirer, rejeter ou synthétiser un nouveau mode d’être à partir d’une thèse qui n’a jamais contenu ou exprimé ce qu’ils ont ressenti comme étant leur expérience historique ?
Keywords: amériques; anthologie; approches et analyses; arts; discipline; histoire et politique; lesbianisme; outils; ouvrages de références; personnes lesbiennes; postmodernisme; régions géographiques; sexualité; thématiques; états-unis; études littéraires